Stochastic modelling and meta heuristic optimization of a batch production system - Harini R.; Indhira K. (Journal of King Saud University: Science, 2024)
Batch production is a modern strategy for manufacturing, especially for products unsuitable for continuous assembly lines. This study proposes a method for analysing one such production facility. Here, we characterize a batch production system as a unique sort of quorum feedback retrial queue deployed under Bernoulli working vacation and outfitted with a secondary, stand-by server. The system’s dynamics are thoroughly examined using the supplementary variable technique, providing insights into its behaviour and performance. Key metrics are determined, and the impact of specific parameters is demonstrated through numerical examples. Furthermore, this research aims to achieve the optimal system cost by employing a variety of optimization approaches. Thus, optimizing costs and identifying key metrics are crucial for enhancing efficiency and profitability in batch production systems. This process ensures that resources are used effectively, service quality is maintained, and overall operational costs are reduced, leading to a more sustainable and profitable production system which helps to make informed decisions.